Engineering Students' Perceptions when Working with Narratives in a Humanities Course (European Journal of Formal Sciences and Engineering, 2021)
This research reveals the change that occurs in a university course when using narratives, which allows facing monumentalism in the classrooms, considering that, in most of them, classes are still being held in a traditional way without taking into account what the students think about the topics covered in the courses. The research is within the qualitative method. The results obtained allow to establish the influence of the course on the learning strategies used by the students, as stable learning indicators, two networks are presented: one corresponding to the use of narratives, and the second, incorporation of the question. Students are motivated to work collaboratively and have a favorable opinion of implementation.
Keywords: narratives, engineer training, humanities education, collaborative work, qualitative research.